Handbook on stiffness & damping in mechanical design - Rivin, Eugene I. (American Society of Mechanical Engineers, 2010)
The book will be useful for practicing engineers working in the field of machine design, design of machine elements, machine dynamics, mechatronics, robotics and precision engineering. It will also be a useful reference for educators, as well as advanced undergraduate and graduate students.
Keywords: Engineering design.; Dynamics, Rigid.; Damping (Mechanics); elektronické knihy; electronic books